Are the effects of EU Cohesion Policy for the Polish regional labour markets worth their costs? - a study based on the results of counter-factual macroeconomic simulations - Janusz Zaleski; Zbigniew Mogiła; Marta Zaleska (European Regional Science Association (ERSA), 2012)
Poland as the main beneficiary of EU Cohesion Policy is an interesting target of analyses regarding the impact of financial interventions on regional economies. Obviously, of special importance for regional communities are effects of EU funds on the labour market. Greater employment- besides counteracting social exclusion- is expected to increase disposable incomes of households and consumption expenditures. This – in turn- is likely to improve well-being of regional inhabitants. Hence, impacts of EU Cohesion Policy on regional labour markets are considered to be the most tangible contribution of the EU financial assistance to higher standards of living for ordinary citizens. The main aim of this paper is to compare and confront the effects of Cohesion Policy on employment and unemployment rates with the costs of the EU financial support in the Polish NUTS-2 regions over the period 2004-2020. Making use of available counterfactual analyses, attempt is made to evaluate the cost-effectiveness of the job creation due to the EU funds. The gathered evidence will be a significant contribution to the debate on the shape of the Cohesion Policy in the new EU financial perspective.
Keywords: R11; 330; EU Cohesion Policy; regional labour market; counter-factual macroeconomic simulations